Digitalisasi UMKM melalui Pelatihan Pengelolaan Produk Berbasis Website, Pemasaran Media Sosial, dan Pemanfaatan Shopee sebagai E-commerce Partner - Susilaningtyas Budiana Kurniawati; Zandra Dwanita Widodo; Atik Lusia; Sulton Tahta Zulfa Adiar Alamshah; Nadiya Nur Rahma Fatika (Pusat Riset dan Inovasi Nasional, 2025)
Digital transformation is a key factor in increasing the competitiveness of micro, small, and medium enterprises (MSMEs), including those managed by women in the agricultural sector. However, the limitations of digital literacy, technology access, and mentoring are still the main obstacles. This article discusses Community Service (PKM) activities carried out by Tunas Pembangunan Surakarta University in the Ngudi Makmur Women Farmer Group (KWT), with the aim of increasing the digital and managerial capacity of group members through two stages of training. The first phase focuses on marketing digitization through website creation, the use of social media, and the use of Shopee as an e-commerce partner. The second stage strengthens the internal aspect with financial training based on the concept of micro business sustainability, especially pricing strategies and improving the quality of processed papaya products. The implementation method uses a participatory approach and hands-on practice so that participants can implement the skills acquired. The results of the activity showed a significant increase in digital literacy, online marketing skills, and financial management skills. The integration of these two trainings strengthens the competitiveness of women MSMEs in the digital economy era and becomes an empowerment model that not only focuses on technology, but also on managerial strengthening to support the sustainability of local community-based businesses.